(untitled) (Innovaciones Educativas, 2026)
Case-based learning (CBL) is a methodology that promotes active learning by improving assertive communication, critical thinking, research skills, and student motivation. This article analyzes the methodologies used by teachers to foster essential communication skills in first-year university students with a special emphasis on effective communication for their academic and professional success. The research, which is qualitative and exploratory-descriptive in nature, included a semi-structured interview to learn about their perspectives on the implementation of CBL. The results indicate that teachers value this methodology because it allows them to reflect on their role and apply practical solutions to real cases. Therefore, it is concluded that CBL is particularly relevant in Life Sciences degrees, where the oral defense of the case strengthens the student’s assertive communication, first with their peers, then with the teacher, and finally with future patients.